Page eight - Nighy, Bill 1949-; Weisz, Rachel 1970-; Fiennes, Ralph 1962-; Hare, David 1947-; Hare, David 1947- (Universal Pictures, 2011)
Johnny Worricker is a long-serving MI5 officer. His boss and best friend Benedict Baron dies suddenly, leaving behind him an inexplicable file, threatening the stability of the organization. Meanwhile, a seemingly chance encounter with Johnny's striking next-door neighbor and political activist Nancy Pierpan seems too good to be true. Johnny is forced to walk out of his job, and then out of his identity to find out the truth